Effect of Probiotics Derived from Lactobacillus DH42 as an Alternative to Antibiotics on the Growth Performance, Gut Health, and Immune Response in Broiler Chickens - Prasad Mandal, Guru; Mandal, Surojit; Mandal, Samiran; Samanta, Indranil; Soren, Stephen (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study was aimed to assess the impact of dietary supplementation with a probiotic (Lactobacillus DH42) on the growth performance, carcass traits, blood biochemical profile, gut microbiome, gut morphology, and immune response of broiler chickens. A total of 162 day-old mixed sex Vencobb 400 broiler chicks were randomly assigned to three dietary groups, each with six replicated pens (n=6), containing nine broiler chickens: 1) basal diet without any growth promoter (CON), 2) basal diet with antibiotic (Bacitracin methylene disalicylate - BMD) at 500 g/ton feed (AGP), and 3) basal diet with probiotic (Lactobacillus DH42) at 1 mL/bird in drinking water (PRO). Body weight, feed intake, and FCR were monitored weekly for 35 days. Blood biochemistry and immune response were evaluated at day 28 and 35 of the trial. Carcass traits, gut microbiome, and gut morphology were assessed at the end of the trial. The results indicated that PRO significantly increased final body weight, average daily gain and improved FCR compared to the control group (p<0.05). There were no significant differences in average daily feed intake, antibody titres, carcass traits and most blood biochemistry parameters, except for cholesterol concentration, which was significantly lower in the PRO and AGP groups compared to the CON group. Both PRO and AGP supplementation led to a significant decrease in caecal E. coli and Salmonella counts and a significant increase in Lactobacillus counts compared to the CON group. Probiotic supplementation also enhanced gut morphology compared to the AGP and CON groups. In conclusion, probiotic supplementation shows promise as an alternative to antimicrobials in broiler production, with beneficial effects on broilers fed an antibiotic-free diet.